Nível do câmbio e crescimento econômico: Teorias e evidências para países em desenvolvimento e emergentes, 1980-2007 - Eliane Cristina Araújo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The article analyses theoretic and empirically the relationship between exchange rate level and economic growth in developing countries. Firstly, the exchange rate policy objectives are discussed, emphasizing the importance of this policy to generate economic growth. Continuing, the article explores the channels through which exchange rates can affect economic growth, highlighting its stimulus to investment, export of non-traditional goods, productivity as well as its compensation to market failures and its stimulus to export income-elasticity. In the empirical part, a measure of exchange rate undervaluation based on Rodrik (2007) is built for 82 developing countries, between 1980 and 2007. This measure is used to investigate the relationship between undervaluated exchange rate and economic growth, by econometrics techniques for panel data. The result of the estimations point out the positive correlation between undervaluated exchange rate and economic growth,confirming the importance of the exchange rate as an instrument to promote economic growth and developing.
Keywords: F31; F43; 330